Current Trends in Radiological Diagnostics and Treatment of the Temporal Bone Pyramid Pathologies - Marzhan Yernarova; Tairkhan Dautov; Bauyrzhan Kaliyev (National Scientific Medical Center, 2024)
Diseases of the middle ear and the temporal bone pyramid remain one of the most common diseases in the structure of otorhinolaryngological pathologies, which have a significant impact on the quality of life of adults and children. Exudative processes, as well as their consequences, become one of the main causes of persistent hearing loss and are characterized by an asymptomatic course with a gradual evolution to chronic forms. It should be noted that in childhood the risk of impaired speech and intellectual development increases, leading to changes in the psycho-emotional status, social maladaptation of the child, and a decrease in the quality of life. Timely and complete diagnosis and high-quality follow-up takes a leading role in preventing the development of conductive hearing loss and other complicated pathologies of the temporal bone pyramid. Purpose of the study. To study the main predisposing factors, methods of radiological diagnosis and dynamic observation of patients, as well as some modern aspects of the treatment of the most common pathologies of the temporal bone pyramid. Methodology. We conducted an analytical review of open access sources from scientific databases such as Scopus, PubMed, Google Scholar, Web of Science, DisserCat, CyberLeninka. Key words used for the search: "chronic otitis media", "cholesteatoma", "mastoiditis", "complications", "magnetic resonance imaging", "DWI", "computed tomography". Publications included in the literature review were full-text articles in English and Russian and dissertations in Russian. Exclusion criteria: brief reports, newspaper articles and personal communications. The search range was 5 years (2018-2023). A total of 108 sources were analyzed, of which 50 met the research objectives and inclusion criteria. Results and conclusions. In the diagnosis of temporal bone pathologies, the gold standard for diagnosis is computed tomography, but non-ionizing research techniques are increasingly used. Indications for the use of magnetic resonance imaging of the temporal bones are constantly expanding, and techniques for merging data with computed tomography data are being increasingly introduced. As a follow-up tool, magnetic resonance therapy is increasingly becoming a priority technique to reduce patient radiation exposure in the long term. In the treatment of complicated forms of diseases, endoscopic and laser correction techniques are used in foreign practice, helping to reduce the risk of recurrence and postoperative complications. Key words: chronic otitis media, cholesteatoma, magnetic resonance imaging, computed tomography, treatment